Quality of end-of-life care of home-based care with or without palliative services for patients with advanced illnesses. Issue 18 (7th May 2021) - Chiang, Jui-Kun; Kao, Yee-Hsin
Abstract : Abstract: Palliative care has improved quality of end-of-life (EOL) care for patients with cancer, and these benefits may be extended to patients with other serious illnesses. EOL care quality for patients with home-based care is a critical problem for health care providers. We compare EOL quality care between patients with advanced illnesses receiving home-based care with and without palliative services. The medical records of deceased patients who received home-based care at a community teaching hospital in south Taiwan from January to December 2019 were collected retrospectively. We analyzed EOL care quality indicators during the last month of life. A total of 164 patients were included for analysis. Fifty-two (31.7%) received palliative services (HP group), and 112 (68.3%) did not receive palliative services (non-HP group). Regarding the quality indicators of EOL care, we discovered that a lower percentage of the HP group died in a hospital than did that of the non-HP group (34.6% vs 62.5%, P  = .001) through univariate analysis. We found that the HP group had lower scores on the aggressiveness of EOL care than did the non-HP group (0.5 ± 0.9 vs 1.0 ± 1.0, P <.001). Furthermore, palliative services were a significant and negative factor of dying in a hospital after adjustment (OR = 0.13, 95%CI = 0.05–0.36, P  < .001). For patients with advanced illnesses receiving home-based care, palliative services are associated with lower scores on the aggressiveness of EOL care and a reduced probability of dying in a hospital.